Body mass index and baseline platelet count as predictive factors in Merkel cell carcinoma patients treated with avelumab - Incorvaia, Lorena; Dimino, Alessandra; Algeri, Laura; Brando, Chiara; Magrin, Luigi; De Luca, Ida; Pedone, Erika; Perez, Alessandro; Sciacchitano, Roberta; Bonasera, Annalisa; Bazan Russo, Tancredi Didier; Li Pomi, Federica; et al. (Frontiers in Oncology, 2023)
Background Merkel cell carcinoma (MCC) is a rare and aggressive skin cancer, associated with a worse prognosis. The Immune Checkpoint Inhibitors (ICIs) avelumab and pembrolizumab have been recently approved as first-line treatment in metastatic MCC (mMCC). The clinical observation of improved outcomes in obese patients following treatment with ICIs, known as the “obesity paradox”, has been studied across many types of tumors. Probably due to the rarity of this tumor, data on mMMC patients are lacking. Patients and methods This is an observational, hospital-based, study to investigate the role of Body Mass Index (BMI) as predictive biomarker of ICI response in mMCC patients treated with avelumab as first-line treatment. The study population included the patients treated from February 2019 to October 2022 in an Italian referral center for rare tumors. Clinico-pathological characteristics, BMI, laboratory parameters (NLR and platelet count), and response to avelumab were analyzed from a MCC System database prospectively collected. Results Thirty-two (32) patients were included. Notably, the presence of pre-treatment BMI ≥ 30 was significantly associated with longer PFS [BMI < 30 Group: median PFS, 4 months (95% CI: 2.5-5.4); BMI ≥ 30 Group: median PFS, not reached; p<0.001)[. Additionally, the median PFS was significantly higher in patients with higher PLT (median PFS: 10 months in the “low PLT” Group (95% CI: 4.9, 16.1) vs 33 months (95% CI: 24.3, 43.2) in the “high PLT” Group (p=0.006). The multivariable Cox regression model confirmed these results. Conclusion To our knowledge, this is the first study that investigates the predictive role of BMI in MCC patients. Our data were consistent with the clinical observation of improved outcomes in obese patients across other tumor types. Thus, advanced age, a weakened immune system, and the obesity-associated “inflammaging”, are key factors that could impact the cancer immune responses of mMCC patients.